|Feb19-07, 01:40 PM||#1|
1. The problem statement, all variables and given/known data
1) Simplify the following Boolean expression:
Y = ABCD – ABD
2. Relevant equations
3. The attempt at a solution
I simplified it in the following way:
Y = ABCD – ABD. (C + 1)
= - ABD
But the answer given in my book is ABD.
|Feb23-07, 12:29 PM||#2|
Could be a typo in the back of the book. In my Discrete Math we are finding almost 20 errors per section. =o) Contact your teacher?
|Feb25-07, 08:56 AM||#3|
Could you specify which textbook and which page? Thanks.
Boolean algebra deals solely in ones and zeroes. It has only three operators: addition, multiplication and negation. There can be no negative numbers. Namely, -1 is not an allowed number, so the concept of subtraction is meaningless is Boolean algebra.
Having said that, Y= ABCD – ABD has either a misprint – instead of +. In this case,
Y= ABCD + ABD = ABD(C+1)=ABD(1)=ABD
Or, possibly, – is given some special meaning.
|Mar5-07, 02:58 PM||#4|
Sorry for the delayed reply. I was busy with my exams. It is a book by an Indian author. Basic Electronics by B.L.Theraja. I think u r right.The question should have been,
Y = ABD - ABCD
|Similar Threads for: Boolean algebra|
|boolean algebra||Calculus & Beyond Homework||13|
|Boolean Algebra||Engineering, Comp Sci, & Technology Homework||1|
|Need Help in Boolean Algebra||Introductory Physics Homework||3|
|boolean algebra||Introductory Physics Homework||6|
|Boolean Algebra AB(A+Bar)=X||Introductory Physics Homework||2|